Study of an Improved Fuzzy Direct Torque Control of Induction Motor - Dong Ming; Tang Yong-qi; Song Hai-liang; Wang Bing-jie (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2013)
The conventional direct torque control will inevitably produce torque ripple because of its way of flux estimates. For the purpose of handling this problem, a new control strategy was presented in this paper. This strategy combined subdivides control with voltage vector and fuzzy logic control in traditional direct torque control. In this model, the fuzzy logic combined the phase angle of the flux, the flux error and torque error as fuzzy variables and classified these fuzzy variables, in order to optimize the choice of voltage space vector, and the same time the traditional PID regulator is replaced by a fuzzy regulator. Simulation results show that, a great improvement torque responses , a great reduction of torque ripples is achieved and the strategy has a better dynamic and steady performance, especially in low-speed area.